2014
DOI: 10.18043/ncm.75.6.376
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Needs Assessment in Wake County, North Carolina

Abstract: A community health needs assessment (CHNA) is a collaborative, systematic process of collecting and analyzing data to learn about the health needs of a community and to implement plans for addressing those needs. Local health departments in North Carolina are required by state law to conduct CHNAs in order to receive accreditation [1]; federal laws also require federally qualified health centers and nonprofit hospitals to conduct CHNAs [2, 3].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…are supporting multidimensional approaches that combine resources of public, private, and philanthropic organizations to increase efficacy and sustainability [14,[18][19][20][21]. As an example, a study of Wake County, NC found that collaboration among multiple stakeholders strengthened efforts by decreasing duplication of efforts, increasing efficient use of resources, increasing capacity, spread the financial and person hours burden across many groups, decreasing budget costs, and increasing expertise expediency of efforts [22]. Despite these successes, it is important for community partnerships to realize that challenges will arise and a memorandum of understanding is essential in order to ensure everyone agrees on common goal(s), expectations, clearly defined responsibilities of each team member [14] planning, framework for community engagement and piloting of the community engaged program [15].…”
Section: Discussionmentioning
confidence: 99%
“…are supporting multidimensional approaches that combine resources of public, private, and philanthropic organizations to increase efficacy and sustainability [14,[18][19][20][21]. As an example, a study of Wake County, NC found that collaboration among multiple stakeholders strengthened efforts by decreasing duplication of efforts, increasing efficient use of resources, increasing capacity, spread the financial and person hours burden across many groups, decreasing budget costs, and increasing expertise expediency of efforts [22]. Despite these successes, it is important for community partnerships to realize that challenges will arise and a memorandum of understanding is essential in order to ensure everyone agrees on common goal(s), expectations, clearly defined responsibilities of each team member [14] planning, framework for community engagement and piloting of the community engaged program [15].…”
Section: Discussionmentioning
confidence: 99%
“…18 These assessments can assist organizations and partnerships in prioritizing resources, especially in areas where resources are limited. [19][20][21] CBPRdriven health needs assessments developed and implemented in partnership with faith-based organizations have demonstrated success in identifying issues relevant to church and community members, including diabetes. [22][23][24] Despite previous successes, 22,23 needs related to SDOHs are less often assessed or identified as top health concerns.…”
Section: Purposementioning
confidence: 99%
“…9 The CBPR-driven CHNA elevates identification of the perspectives, preferences, and priorities of the communities with whom interventions are developed. 10 This approach uncovers issues of local relevance that can be applied to interventions addressing the social determinants of health.…”
mentioning
confidence: 99%